Description of Non-Traditional Teaching Techniques Used In the Classes of the 3rd Class Native Language - Adizova Nigora Bakhtiyorovna; Ozodova Madina (Research Parks Publishers, 2021)
In this article, it was noted that the organization of lesson classes, strict adherence to the printing techniques and techniques of teaching, taking into account the age, level and ability of Primary School students to receive knowledge